Microsoft SQL Server Analysis Services Multidimensional Performance and Operations Guide - Kejser, Thomas (Microsoft, 2015)
This book consolidates two previously published guides into one essential resource for Analysis Services developers and operations personnel. Although the titles of the original publications indicate SQL Server 2008 R2, most of the knowledge that you gain from this book is easily transferred to other versions of Analysis Services, including multidimensional models built using SQL Server 2012...